Diagnosis of overtraining: What tools do we have? - Urhausen, A.; Kindermann, W. (Sports Medicine, 2002)
The multitude of publications regarding overtraining syndrome (OTS or 'staleness') or the short-term 'over-reaching' and the severity of consequences for the athlete are in sharp contrast with the limited availability of valid diagnostic tools. Ergometric tests may reveal a decrement in sport-specific performance if they are maximal tests until exhaustion. Overtrained athletes usually present an impaired anaerobic lactacid performance and a reduced time-to-exhaustion in standardised high-intensity endurance exercise accompanied by a small decrease in the maximum heart rate. Lactate levels are also slightly lowered during submaximal performance and this results in a slightly increased anaerobic threshold. A reduced respiratory exchange ratio during exercise still deserves further investigation. A deterioration of the mood state and typical subjective complaints ('heavy legs', sleep disorders) represent sensitive markers, however, they may be manipulated. Although measurements at rest of selected blood markers such as urea, uric acid, ammonia, enzymes (creatine kinase activity) or hormones including the ratio between (free) serum testosterone and cortisol, may serve to reveal circumstances which, for the long term, impair the exercise performance, they are not useful in the diagnosis of established OTS. The nocturnal urinary catecholamine excretion and the decrease in the maximum exercise-induced rise in pituitary hormones, especially adrenocorticotropic hormone and growth hormone, and, to a lesser degree, in cortisol and free plasma catecholamines, often provide interesting diagnostic information, but hormone measurements are less suitable in practical application. From a critical review of the existing overtraining research it must be concluded that there has been little improvement in recent years in the tools available for the diagnosis of OTS.